Bound to be Free: Evangelical Catholic Engagements in Ecclesiology, Ethics, and Ecumenism (Modern theology, 2006)
Book reviewed: Bound to be Free: Evangelical Catholic Engagements in Ecclesiology, Ethics, and Ecumenism by Reinhard Hütter (Grand Rapids, Michigan: Wm. B. Eerdmans Publishing Company, 2004) x + 313 pp. Reviewed by Jean Porter Department of Theology The University of Notre Dame 130 Malloy Hall Notre Dame, IN 46556 USA